Pemberdayaan Ekonomi Berbasis Budaya Lokal Batik Tulis di Desa Bogoharjo Kecamatan Ngadirojo Pacitan - Untari, Dwi; Aorta, Dian Tias (YASIN, 2025)
This study is motivated by the development of the batik tulis (hand-drawn batik) industry, which is quite good in Bogoharjo Village, playing an important role in supporting family economies, especially for women's groups. The aim of this research is to understand the development of the batik tulis industry as a form of economic empowerment based on local culture. This research employs a qualitative descriptive approach with data collection techniques including participatory observation, in-depth interviews, and documentation. The research location is in Bogoharjo Village, with informants consisting of village officials, batik tulis business owners, and community members directly involved. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The results indicate that local cultural-based economic empowerment through batik tulis is very feasible in Bogoharjo Village, as the batik tulis industry absorbs a significant amount of female labor around the industrial houses. The conclusion of this study emphasizes that each batik tulis industry has unique characteristics and faces various inhibiting and driving factors in the process of economic empowerment based on local culture. This research is expected to serve as a reference in the development of knowledge, particularly on related topics. Practically, this research is anticipated to provide input to stakeholders in the batik tulis industry in Bogoharjo Village, as well as to village government officials as initiators of community empowerment programs. Furthermore, this study is expected to provide useful information and an overview of batik tulis from a different perspective.